Public Health Messages and Weight-Related Beliefs: Implications for Well-Being and Stigma - Hoyt, Crystal L.; Burnette, Jeni L.; Thomas, Fanice N.; Orvidas, Kasey (Frontiers in Psychology, 2019)
Across two studies, we examined the double-edged sword hypothesis, which outlines effects of weight-related beliefs and public health messages on physical and mental health. The double-edged sword hypothesis proposes that growth mindsets and messages (weight is changeable) predict reduced well-being and stigma via an increase in blame, but also predict greater well-being via an increase in efficacy and less stigma via a reduction in essentialist thinking. We tested this model in a correlational study (N=311) and in an experimental study, randomly assigning participants (N=392) to different weight-based public health messages. In Study 1, growth mindsets predicted greater onset blame and more offset efficacy. Blame did not predict any of the outcomes. However, offset efficacy predicted reduced risk for eating disorders, fewer unhealthy weight control behaviors, and less psychological distress. And, growth mindsets had a negative indirect effect on outcomes. In Study 2, we experimentally demonstrated that a changeable, relative to a fixed, message about the nature of weight, designed to also reduce blame, indirectly decreased eating disorder risk, unhealthy weight control behaviors, body shame, and prejudice through increased offset efficacy and decreased social essentialism. This work contributes to our theoretical understanding of the psychological consequences of weight beliefs and messages on well-being and stigma.